Hellp syndrome. Experience at Edgardo Rebagliati Martins Hospital, ESSALUD. - Huerta Sáenz, Igor (2015)
oBJECtivE: To describe the clinical and epidemiologic characteristics, and maternal and perinatal morbidity and mortality caused by HELLP syndrome. dESign: Descriptive retrospective study. Setting: Edgardo Rebagliati Martins National Hospital, Rebagliati Health Network, EsSalud, Lima, Peru, a teaching hospital. Participants: Pregnant women with HELLP syndrome and their perinates. Interventions: We studied all HELLP syndrome cases attended from January 1, 1998 through December 31, 2002. Data was processed with Excel, MS Word programs and for statistical analysis we used SPSS for Windows software, version 10,7. main outcome measureS: Prevalence, characteristics, maternal and perinatal complications due to HELLP syndrome. Rsults: We had 67 cases of HELLP syndrome during the period studied with prevalence of 0,16/1 000 births. Incidence among preeclamptic women was 3,9% and 10% among women with eclampsia. Mean maternal age was 32,7 years, 60% between 25 and 34 yearold, 94% mixed race, 68,6 multiparae and 98,5% with prenatal control; 97% presented hypertension, 73% headache, and 49% epigastric pain. Maternal complications consisted in renal insufficiency in 20,8%, pleural effusion in 11,9%, and liver hematoma in 4,5%. There were 3 maternal deaths. Mean maternal hospitalization at the intensive care unit was 5 days. From the 70 siblings, 3 were fetal deaths and 95,5% were born by cesarean section. Mean gestational age was 34,6 weeks, 66% preterm. Mean weight was 1 981,4 g, 46,3% low birth weight, 34,3% small for gestational age; 14,9% needed positive pressure and 2,9% cardiac massage; 31,3% presented hypoglicemia, 19,4% sepsis, 17,9% hyaline membrane disease; 44% required intensive care, remaining an average of 13 days. We registered 5 neonatal deaths. Perinatal death rate due to HELLP was 11,4%. Conclusions: HELLP syndrome caused grave maternal and perinatal complications; products were preterm, low birthweight, adequate for gestational age. In our population we suggest high suspicion of HELLP syndrome development in women 32 year-old, multiparous, with early third trimester pre-eclampsia or eclampsia, and without previous history of this complication.